Don't turn out the lights - Minier, Bernard (Minotaur Books, 2016)
""You did nothing." Christine Steinmeyer thought the anonymous suicide note she found in her mailbox on Christmas Eve wasn't meant for her. But the man calling in to her radio show seems convinced otherwise. Bit by bit, strange things keep happening ... it's as if someone has taken control of her life. Everything holding Christine's life together crumbles until all that is left is an unimaginable nightmare. Martin Servaz is on leave in a clinic for depressed cops, haunted by his childhood sweetheart Marianne's kidnapping by his nemesis, the psychopath Julian Hirtmann. One day, he receives a key card to a hotel room in the mail--the room where an artist committed suicide a year earlier. Someone wants him to get back to work, which he's more than ready to do, despite his mandatory sick leave ... What if the people closest to us are not what they seem? What happens when someone takes control of your life and your relationships? And what is hiding in the darkness? Don't turn out the lights. If you do, prepare for the worst"--